1998
DOI: 10.1063/1.477337
|View full text |Cite
|
Sign up to set email alerts
|

Bond fluctuation model of polymers in random media

Abstract: Conventional descriptions of polymers in random media often characterize the disorder by way of a spatially random potential. When averaged, the potential produces an effective attractive interaction between chain segments that can lead to chain collapse. As an alternative to this approach, we consider here a model in which the effects of disorder are manifested as a random alternation of the Kuhn length of the polymer between two average values. A path integral formulation of this model generates an effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…However, other models, such as the Yamakawa model and the Marko-Siggia model, also fit into our general formulation. For the Kratky-Porod wormlike chain model, the stiffness matrix, chirality vector and constant term in (2) are defined as 28 (50) where χ is known as the stiffness parameter. The definitions of the stiffness matrix, chirality vector and constants for the Yamakawa model and Marko-Siggia models can be found in 28 .…”
Section: Examples and Discussionmentioning
confidence: 99%
“…However, other models, such as the Yamakawa model and the Marko-Siggia model, also fit into our general formulation. For the Kratky-Porod wormlike chain model, the stiffness matrix, chirality vector and constant term in (2) are defined as 28 (50) where χ is known as the stiffness parameter. The definitions of the stiffness matrix, chirality vector and constants for the Yamakawa model and Marko-Siggia models can be found in 28 .…”
Section: Examples and Discussionmentioning
confidence: 99%
“…where the expectation values can be calculated, as before, using the propagator (13) with the Green function (33). For calculation of the rotationally invariant quantity G(s, s ′ ) = G(s − s ′ ), however, the Green function ∆(s, s ′ ) + C must be just as good a Green function satisfying Neumann boundary conditions as ∆(s, s ′ ).…”
Section: Correlation Function Up To Four Loopsmentioning
confidence: 99%
“…. 0 are evaluated by performing all possible Wick contractions with the basic propagator (13) and the Green function (33) of the unperturbed action (37). The relevant loop integrals I i and H i are calculated with our regularization rules when necessary and are listed in Appendices A and B.…”
Section: Partition Function and All Moments Up To Four Loopsmentioning
confidence: 99%
See 1 more Smart Citation
“…For some basic polymer models, ''closed-form'' path integral formulas have been derived for the probability distributions of loop length, 21 segmental orientations, 22 trajectories of a segment, 23 radius of gyration, 24 end-to-end position and distance, [25][26][27][28][29][30][31][32] and moments. 29,32,33 However, for sophisticated models, the evaluation of path integrals can be hard to handle, and usually requires extensive numerical calcula-tions. In previous work we showed that the probability density function ͑PDF͒ of the end-to-end relative position and orientation for the most general model of an inextensible semiflexible polymer chain can be obtained by either solving a diffusion equation or convolving PDFs for short segments of the chain.…”
Section: Introductionmentioning
confidence: 99%